Legal solutions regarding the management of game and hunting grounds in R. North Macedonia, R. Serbia, R. Croatia, R. Slovenia and R. Bulgaria - Cokoski, Kristijan; Maletic, Vladimir; Tanoski, Vladimir; Risteski, Mihajlo ("Hans Em" Faculty for Forest Sciences, Landscape Architecture and Environmental Engineering, Skopje, 2022)
The influence of elevation on the forest development and also on more structural elements are evident. This paper research the influence of elevation on the relationship between diameter at breast height (DBH), tree height (H), crown length (L) and steam volume (V). In the area of National Park Pelister in North Macedonia, we established 6 circle experimental plots (EP) at 1150 m a.s.l., 7 at 1350 m a.s.l. and 9 at 1550 m a.s.l. total 22 EP with an area of 500 m2 each of them in the evenage Pinus peuce Gris. stands with an average age of 90 years. It was measured DBH, tree height, and crown length at 481 trees in all EP. We determined the connection between DBH and H thought height model from Prodan. It was prepared nonlinear (polynomial) regression for the relation between DBH and L and nonlinear (Power) regression for the relation between DBH and V. Also, were calculated quadratic mean of DBH, average Loray height, average crown ratio, and the density of the stands. The steam volume was calculated with a formula from the volume table from Parishko for Pinus peuce Gris. The relationship between DBH and H, L, V was tested with Pearson correlation and root mean square deviation (RMSE). The differences between data of H, L, V from the EP were tested with analysis of variance (ANOVA) with a single factor. All statistical analyses were done with Excel, Statsoft Statistica, R (CranRstudio) software. The density of stands is 490, 429 and 409 trees per ha on 1150 m, 1350 m and 1550 m a.s.l. respectively. The average DBH is 39.8 cm, 46.5 cm and 45.5 cm and Loray height is 23.9 m, 24.1 m and 22.6 m at 1150 m, 1350 m and 1550 m a.s.l. respectively. Crown ratio points out different results on the different elevation, thus average value of 40.5 %, 43.7 %, 39.3 % at 1150 m a.s.l., 1350 m a.s.l. and at 1550 m a.s.l. respectively. The differences between data are significantly p<0.05 and F of 3.4, at data of H, with p<0.05 and F 3.2 for data of L and p<0.05 with F of 9.7 for data of V. In that way, H has a bigger regression model at a lower elevation, the tree has a longer crown length at lower elevation and also has more biomass at lower elevation. The regression model of Prodan for H has а significance correlation index of 0.85, 0.80, 0.79 and RMSE of 6.55, 8.04, 6.18 for 1150 m, 1350 m and 1550 m respectively. The polynomial regression model for the connection between DBH and L has a correlation of 0.80, 0.81, 0.69 and RMSE of 59 8.31, 10.40 and 10.77 for 1150 m, 1350 m, 1550 m respectively. The power regression model for DBH and V has a correlation of 0.99, for all elevations and RMSE of 1.08, 1.48, 0.75 for 1150, 1350, 1550 m respectively. From the results can be concluded that the elevation has an influence on DBH, H, L and V as structural elements and also has an influence on the whole development of stands. It can be said that at higher elevation trees has a smaller height, DBH, volume and have longer crown length than trees at lower elevation.
Keywords: : structural elements; elevation; Pinus peuce Gris.; diameter at breast height; height of trees; crown length